Bioensayo para la detección de PHYTOPHTHORA CINNAMOMI EN EL SUELO DE RODALES AFECTADOS POR LA SECA DE QUERCUS - HERMOSO, R; SÁNCHEZ, E; TRAPERO, A (III Congreso Forestal Español, 2001)
The isolation of Phytophthora spp. from soil samples is often difficult, even using indirect methods which combine baiting techniques and selective media. Apple or avocado fruits or carnation petals are some of the most common baits used for the isolation of P. cinnamomi from infested soils where Quercus ilex and Q. suber have been affected by root rot and decline. However, the use of these baits has serious limitations because of the contamination by several fungi and bacteria. The aim of this work was to improve the baiting technique for the pathosystem P. cinnamomi / Quercus spp. The effect of different factors, including several baits (leaves, fruits, cotyledons, radicles), the soil:water dilution, and the incubation time, was checked using a soil mixture artificially infested with several isolates of P. cinnamomi. The most effective baiting method included baits of eucalyptus phyllodium pieces (Eucalyptus globulus and less effective E. camaldulensis), 1:6 soil:water relation, and 4 days incubation period. The efficiency of this method has been tested for the detection of P. cinnamomi in naturally infested soil samples from fields where the root rot caused by this pathogen had been previously diagnosed
Keywords: phytophthora cinnamomi; Quercus decline; soil detection

First record of Phytophthora cinnamomi on cork and holm oaks in France and evidence of pathogenicity - Robin, Cécile; Desprez-Loustau, Marie-Laure; Capron, Gilles; Delatour, Claude (Ann. For. Sci., 1998)
In 1995 and 1996, a survey for the presence of Phytophthora cinnamomi in cork and holm oak sites in southeastern France was carried out. Twenty-four sites were chosen. Tree decline severity and other characteristics were assessed. Subplots of four trees were more fully investigated: relative soil water content was assessed and Phytophthora isolation was attempted from soil samples. When cortical lesions were observed, isolations were carried out from infected tissues. In six cork oak and one holm oak sites, P. cinnamomi was isolated from soil or trunks. All the different isolates obtained in 1995 were aggressive on cork and holm oaks. However, these species were less susceptible than Castanea sativa and more susceptible than Q. rubra. These results confirm the pathogenicity of P. cinnamomi towards Mediterranean oaks and its possible involvement in the decline process of these species.
Keywords: Cork; phytophthora cinnamomi; Quercus ilex; Quercus suber; soil detection; trunk cankers